2010
DOI: 10.1016/j.jweia.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

On the galloping instability of two-dimensional bodies having elliptical cross-sections

Abstract: Keywords:Galloping Elliptical cross-section bodies Wind tunnel Galloping, also known as Den Hartog instability, is the large amplitude, low frequency oscillation of a structure in the direction transverse to the mean wind direction. It normally appears in the case of bodies with small stiffness and structural damping, when they are placed in a flow provided the incident velocity is high enough. Galloping depends on the slope of the lift coefficient versus angle of attack curve, which must be negative. Generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 10 publications
2
24
0
1
Order By: Relevance
“…In the case of galloping, the literature is biased through prone to gallop bodies; a large number of papers dealing with the galloping properties of a wide spectrum of geometries have been published [9,[15][16][17][18]. Other cases of interest are the twodimensional bodies with highly attenuated oscillations and those which do not gallop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of galloping, the literature is biased through prone to gallop bodies; a large number of papers dealing with the galloping properties of a wide spectrum of geometries have been published [9,[15][16][17][18]. Other cases of interest are the twodimensional bodies with highly attenuated oscillations and those which do not gallop.…”
Section: Introductionmentioning
confidence: 99%
“…Such analysis has been performed at IDR/UPM experimental facilities and the galloping properties of different families of two-dimensional bodies with different cross-section shapes have been published (triangles, rhombi, biconvex, elliptical, rectangles, etc. [15][16][17]). These bodies show transverse galloping instability in certain ranges of the angle of attack, and they are stable outside these specific limits.…”
Section: Introductionmentioning
confidence: 99%
“…where, F d , F l = Mean drag and lift forces, respectively; C d , C l = Mean drag and lift force coefficients, respectively; Wref = Reference width = b" for C d , d" for C l ; pref = Reference pressure at measurement levels, as mentioned in Equation (1). Torsion (T) for all angles of wind incidence with respect to the origin wasevaluated using the measured pressures along with lever arms at each level.…”
Section: Coefficientsmentioning
confidence: 99%
“…The investigation of simple nonlinear FSI systems is an active one and recent experimental work has shown that a single degree of freedom pendular disk in a cross flow exhibits bistability (Obligado et al 2013). An entire field of literature exists on the rotational galloping and torsional flutter of bluff cylinders due to their prevalence in civil and industrial engineering (Nakamura 1990;Van Oudheusden 1996;Robertson et al 2003;Alonso et al 2010). Understandably these analyses are mostly focused on preventing such large amplitude motions and generally feature quasi-static analysis and static experiments at high Reynolds number.…”
Section: Introductionmentioning
confidence: 99%